Computer Control System for Heavy Machine Fixtures Motion and its Application for Automatic Generation of Cutting Tools Trajectories According to the Given Criteria - Płonecki, L.; Trąmpczyński, W.; Gierulski, W.; Cendrowicz, J.; Sokołowski, K. (Engineering Transactions, 2000)
The computer control system for heavy machine (loaders, excavators) fixtures motion is presented and discussed in the paper. It enables the automatic generation of cutting tool (buckets) trajectories to fulfil the assigned criteria, for example the minimum unit energy criterion or the maximum disposable force criterion. The performance of the system was investigated using the laboratory stand built in semitechnical scale and the model cohesive soil. The tool shape in the stand corresponds to the shape of the bucket of the Waryński excavator K-lll.